Performance analysis of load balancing scheme in LTE network planning using relay / Azmi Abang Abdul Rahim - Abang Abdul Rahim, Azmi (2014)
Long Term Evolution (LTE) marketed as fourth generation is a standard for wireless communication of high speed data for mobile phones and data terminals. LTE is based on the GSM/EDGE and UMTS/HSP A network technologies to increase the capacity and speed using a different radio interface together with the core network improvements [6). The recent increase of mobile data usage and advent of new applications have greatly motivated the 3rd Generation Partnership Project (3GPP) to work on the L TE. Relay is one of the features being proposed for the 4G LTE system. The aim of LTE relaying is to enhance both coverage and capacity. As cell edge performance is becoming more critical, with some of the technologies being pushed towards their limits, it is necessary to look at solutions that will enhance performance at the cell edge for a comparatively low cost. One solution that is being investigated and proposed is that of the use of LTE relays. The purpose of this project is to analyze performance of load balancing scheme in LTE network planning using relays in order to improve the traffic of the system. In addition, enhanced signal quality LTE relay is not experiencing signal degradation but reduced to noise ratio when using a repeater. However, low-power transmitter that can cause the coverage area of relay nodes will be small. Therefore, the performance of relay movement may be limited by the load imbalance. In this study, we present a practical solution to this problem with ENB transmits power to the implementation of the relay node placement that has been enhanced with load balancing between macro cells and relay cells. Comprehensive system level simulations confirm that the proposed solution by using the relay can improve the traffic of the system that has been calculated in the RSS macro, RSS relay, dropcall and handover.